Epidemiology of major lower extremity amputations in individuals with diabetes in Austria, 2014–2017: A retrospective analysis of health insurance database. (December 2020) - Aziz, Faisal; Reichardt, Berthold; Sourij, Caren; Dimai, Hans-Peter; Reichart, Daniela; Köhler, Gerd; Brodmann, Marianne; Sourij, Harald
Highlights: The rate of major lower extremity amputations in Austria meets the OECD average. Major lower extremity amputation rates remained consistent between 2014 and 2017. All-cause mortality rates after major lower extremity amputations are high in Austria. The risk of all-cause mortality increased significantly in the presence of comorbidities. Charlson comorbidity index may be utilized as a risk stratification tool in this population. Abstract: Aims: To describe the incidence, mortality, and trend of major lower extremity amputations (LEA) and to assess risk factors of all-cause mortality after major LEA in individuals with diabetes. Methods: Procedure codes of major LEA were extracted from the Austrian Health Insurance database (N = 507, 180) during 2014–2017 to estimate crude and age-standardized rates per 100, 000 population. Short- (30-day, 90-day) and long-term (1-year, 5-year) all-cause mortality after major LEA was estimated from the date of amputation till the date of death. Results: The age-standardized rate of major LEA was 6.44 with an insignificant annual change of 3% (p = 0.825) from 2014 to 2017. Cumulative 30-day mortality was 13.5%, 90-day 22.0%, 1-year 34.4%, and 5-year 66.7%. Age, male sex, above-knee amputation, Charlson index, and heart failure were significantly associated with both short- and long-term mortality. Cancer, dementia, heart failure, peripheral vascular disease, and renal disease were associated with long-term mortality. Conclusions: The rate of major LEA in individuals with diabetes remained stable during 2014–2017 in Austria. Short- and long-term mortality rates were considerably high after major LEA. Old age, male sex, above-knee amputations, and Charlson Index were significant predictors of both short- and long-term mortality and comorbidities were significant predictors of long-term mortality only.